Pengaruh Ukuran Perusahaan, Profitablitas Dan Kinerja Lingkungan Terhadap Pengungkapan Corporate Social Responsibility Disclosure - Hidayat, Muhammad Fery (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to re-calculate empirically the effect of Company Size, Profitability and Environmental Performance on Corporate Social Responsibility Disclosures in mining companies in Indonesia. The population of this study are mining companies listed on the Indonesia Stock Exchange in 2018. The sample selection method uses a purposive sampling technique based on certain criteria. The total number of companies used in this study were 30 companies, the data used were secondary data in the form of company annual reports. The data analysis technique used is linear regression analysis with the result that Company Size, Profitability and Environmental Performance have no effect on Corporate Social Responsibility Disclosure.